Tarian mongigol-sumundai momogun rungus di sabah: Analisis konsep persembahan dan ragam gerak - Victor B. Pangayan (Gendang Alam, 2020)
The Mongigol-Sumundai dance is a traditional Momogun-Rungus choreography that lives in the Kudat, Pitas and Sandakan districts of the north west coast of Sabah. Often this dance is performed at weddings, Kaamatan Festival and Moginakan Festival ceremonies. The key focus of this analysis is the idea of dance performance by Mongigol-Sumundai and the diversity of movements used in this dance performance. The results of observations and studies have shown Mongolian-Sumundai dance to have two performance concepts and each concept has a different function. The researcher was also able to classify 12 moving styles that are commonly used for the Mongigol-Sumundai dance performances and the entire range of these movements can be evaluated by means of the Laban Eight Effort Movement in terms of movement efficiency. Such a research is essential for us to deepen and understand the concept of performance and the diversity of movements in the dance performance of Mongigol-Sumundai.